The EU as Regional and Global Player - Oana Emiliana Tatarcan (CES Working Papers, 2015)
European Union is a family of democratic European countries working together to improve the lives of their citizens and to build a better world. Family squabbles and occasional crises are the headlines, but away from the cameras the EU is a remarkable success story. Moreover, it is the biggest donor of development aid in the world and has pledged that he would be willing to collaborate and provide support as long as it will require member needy. The EU needs to strengthen its global presence and to respond more quickly and effectively to events that occur frequently. The European Union could be a model to determine the final disappearance of the state system and its replacement by a new community centers and stronger political and economic networks.
Keywords: F50; 330; globalization; state; conflict; development; economic